Trends in Steroid Response Among Children With Idiopathic Nephrotic Syndrome (Iranian Journal of Kidney Diseases, 2014)
Introduction. Idiopathic nephrotic syndrome (INS) is a common chronic illness in childhood and is initially treated with corticosteroids. Recent reports indicate that the incidence of steroid resistance and focal segmental glomerulosclerosis is on the rise. However, these reports involved different ethnic populations. The purpose of this study was to compare the characteristics of INS in Iranian children in different periods. Materials and Methods. A retrospective chart review of children admitted with the diagnosis of new-onset INS was performed. Patients were divided into two groups based on date of presentation periods of 1991 to 2002 and 2005 to 2012. Steroid resistance was defined as persistent proteinuria (2+ and more) within 8 weeks of oral corticosteroid treatment. Results. A total of 238 children included in this study (119 in each group). There was an insignificant decrease in the frequency of steroid resistance, along with an insignificant change in histopathology towards focal segmental glomerulosclerosis. Conclusions. These findings indicate that in contrast to other reports of INS from various ethnic compositions, a tendency to steroid resistance is still arguable in the population of Iranian children.